PERAN ORANG TUA DALAM MENGEMBANGKAN SIKAP KREATIVITAS ANAK USIA DINI DI MASA PANDEMI - Khusnul Khotimah; Dwi Bhakti Indri M (INCARE, International Journal of Educational Resources, 2022)
This article aims to reveal the role of parents in developing early childhood creativity in pandemic times. Where at this time of emigrants children's learning activities are carried out at home. So the role of parents is very important in helping and guiding children in learning activities at home. Especially activities in developing children's creativity. This article uses the library research method by elaborating on books and journals. This article uses content analysis techniques in several books and journals. The results of this article are: the role of parents is to provide freedom of creativity, provide motivation, provide supervision, respect the child's opinions, familiarize children to face challenges. So that this role can be carried out in developing children's creativity at home during this pandemic.